(untitled) (Verse Version, 2025)
The academia has traced the cultural roots of the poetics of Robert Bly, a leading figure of the American “Deep Image” school, to foreign sources, such as European Surrealism, psychological unconscious theories, European mysticism, and Chinese Daoist philosophy. However, an examination of Bly’s own poetics reveals his emphasis on nativist consciousness and solitude, highlighting intricate connections with transcendentalism—a cornerstone of American indigenous culture. This discovery will contribute to a deeper understanding of Bly’s poetic spirit and its place within modern and contemporary American poetry.